PERSEPSI PENGUSAHA USAHA MIKRO KECIL MENENGAH TERHADAP JASA AKUNTAN PUBLIK (Studi Empiris Pada Disperindag Bukittinggi) - Azima, Fauzan; Anisma, Yuneita; Anggraini, Lila (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
SMEs or Micro, small and medium enterprise have a role in creating new jobs. And can complement the activities of tourism in Bukittinggi. SMEs play a role in its development is very important and very large in advancing the growth and development of the indonesian economi, and can absorb the unemployed to return to work. This study aims to determine differences in perceptions of entrepreneurs ukm consisting or micro, small and medium enterprise to public accounting service. (Empirical Studies on cooperative departement of industry and commerce Bukittinggi )And to analyze the data in this case the researchers used computer assistance program spss version 21, where the sample used that SMEs in bukittinggi with about 100respondents consisted of 89 micro enterprises, 9 small businesses, and 2medium businesses. The formula used to determine the sample slovin, as well as a sampling technique by purposive sampling. Data collection through questionnaires. According to a study that researchers do to enterpreneurial SMEs, and the results of the study researchers can concluded that the larger the scale of business in bukittinggi the perception of accounting service, auditing service, tax service, and management service will be higher.Keywords:Perception, accounting service, auditting service, tax service, management consultation service.